Pengaruh Store Atmosphere dan Service Quality Terhadap Keputusan Pembelian Ulang Dengan Kepuasan Konsumen sebagai Variabel Intervening Pada Pelanggan Kaldi Coffee Shop Pekanbaru - Feblin Isma Anjelika; Syofiatul Safitri (LPPM Universitas Sains dan Teknologi Komputer, 2026)
Coffee shops in Indonesia are experiencing rapid growth, making them one of the most dynamic and competitive sectors in the food and beverage industry. This study was conducted among customers of Kaldi Coffee Shop in Pekanbaru to determine the influence of store atmosphere and service quality on repurchase decisions, with customer satisfaction as an intervening variable. The research sample consisted of 99 customers of Kaldi Coffee Shop in Pekanbaru, selected using purposive sampling based on specific criteria. Data were collected through a questionnaire and subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The test results indicate that Store Atmosphere has a positive and significant effect on Customer Satisfaction and a significant effect on Repurchase Decision. Service Quality was also found to have a positive and significant effect on Customer Satisfaction, as well as a significant effect on Repurchase Decision. Customer Satisfaction was found to have a significant effect on Repurchase Decision. Indirectly, Store Atmosphere has a significant effect on Repurchase Decision through Consumer Satisfaction, and Service Quality has a significant effect on Repurchase Decision through Consumer Satisfaction. This indicates that the customer experience, supported by an aesthetically pleasing cafe atmosphere and excellent service, is capable of building consumer satisfaction, which in turn becomes the primary driver of repurchase loyalty at Kaldi Coffee Shop Pekanbaru.